Immunization of Balb/c mice with modified auto-antigens for induction of autoimmune sialoadenitis - Unterkircher,Carmelinda Schmidt (2007)
Sjögren's syndrome is an autoimmune disease characterized by sialoadenitis and elevated titers of autoantibodies. To assess whether it is possible to induce inflammatory changes in salivary gland tissues, a series of immunizations in Balb/c mice have been undertaken, using salivary gland extract, modified or not, added to several adjuvants. Mice's humoral immune response to salivary gland antigens was monitored by ELISA. Inflammatory cells infiltrating gland tissue were seen 3 months after immunization with salivary gland extract modified with pepsin (AgGp) and metaperiodate (AgGMp). Although pathological progression was not observed, the histopathological picture was similar to the initial phase of Sjögren's syndrome. In addition, a monoclonal antibody reactive with 3 gland polypeptides and anhydrase carbonic II was rescued among B cells from immunized mice. Thus, immunizations with modified autoantigens were able to initiate pathological damage to glandular tissue and stimulate the proliferation of auto-reactive B cells.